Management of cardiovascular system in normal subjects working for NTT: Re-evaluation of the standard 12-lead electrocardiogram - Asai, Ryuji; Hosokai, Hiroaki; Yagi, Hiroshi; Suzuki, Shinichiro; Tamura, Shizuo (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1991)
In order to evaluate the clinical significance of the standard 12 lead electrocardiogram (ECG) in advanced aging and in males and females, PQ interval, QRS duration, frontal QRS axis, and heart rate at rest in 12, 528 workers aged 30 to 59 years, who underwent health examinations at the NTT Tokyo Health Care Center during 1989. Results were as follows : a) In males PQ interval and QT were prolonged, and QRS frontal axis was shifted leftward with advansing age. Heart rate, however, showed no association. There were difference in PQ interval, QRS duration and QT between males and females. b) The prevalence of conduction system abnomalities increased in the order : first degree a-v block> sinus bradycardia> incomplete right bundle branch block. The occurrence of WPW syndrome was 0.18% of all subjects. c) Of abnormalities in wave form and amplitude, 37% was represented by left ventricular hypertrophy (LVH). This suggests the necessity for modifications in current diagnostic criteria for the ECG diagnosis of LVH. d) A total of 696 cases (5.6%) received a diagnosis of abnormal ECG as a final decision by cardiovascular system specialists. e) Either Holter ECG or echocardiography analysis was performed for cases which revealed either VPC and LVH with ST-T change. Five of 19 subjects who had VPC required antiarrythmic drug. Thirty of 90 subjects who had LVH with ST-T change had suspected hypertrophic cardiomyopathy. These results may play an important role in the use of the ECG in the health examination in work place.